Апрельская буря: лирика / Елена Нестерова - Нестерова Елена Васильевна (Книжное издательство, 1979)
Экземпляры: КХ (20120503) / Инвентарный номер: 703762 / Цена: 0.25 / Сис.шифр: Р2 / Авт.знак: Н 56 / ГРНТИ: 17 / ББК: 84(2)